EARNINGS PERSISTENCE : THE INFLUENCE OF CORPORATE STRUCTURE AND PERFORMANCE VOLATILITY (STUDY AT KOMPAS 100 FOR 2020 – 2023) - patricia diana; Gabriel Brian Lawe Ike Leyn (Ultimaccounting Jurnal Ilmu Akuntansi, 2026)
Introduction/Main Objectives: Earnings persistence is an important indicator that reflects a company’s ability to manage its resources effectively in order to generate sustainable profits in the future. Persistent earnings provide useful information for corporate decision-making, particularly in formulating strategic policies, and for investors in evaluating investment opportunities. This study employed a purposive sampling method, with the research sample consisting of companies consistently listed in the Kompas100 Index during 2020–2023. The study used secondary data obtained from companies’ financial statements, which were analyzed using multiple linear regression. The novelty of this study lies in the measurement of the market concentration variable, which is constructed by comparing the scale of the sample company with that of firms in the same industry, thereby allowing the company’s size to be interpreted proportionally relative to comparable industry peers. The results indicate that sales volatility has a significant negative effect on earnings persistence, while market concentration has a significant positive effect. In contrast, ownership concentration and operating cash flow do not have a significant effect on earnings persistence. Simultaneously, sales volatility, ownership concentration, market concentration, and operating cash flow have a significant effect on earnings persistence. Keywords: Earnings Persistence; Market Concentration; Operating Cash Flow; Ownership Concentration; Sales Volatility